2019
DOI: 10.12688/f1000research.20704.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between postpartum depression and lactation status at a Japanese perinatal center: A cross-sectional study

Abstract: Background:  Some studies have demonstrated that breastfeeding can protect mothers from postpartum depression; therefore, we examined the association between postpartum depression and lactation status at one month after delivery at a Japanese perinatal center. Methods: We reviewed the obstetric records of all (total 809) nulliparous healthy women with vaginal singleton delivery at 37-41 weeks’ gestation at our institute between July 2018 and June 2019. A face-to-face interview with the women was conducted on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(13 reference statements)
0
1
0
Order By: Relevance
“… 28 Although breastfeeding can protect individuals from postpartum depression, it was not found to be associated with incomplete breastfeeding in some studies, and there were other risk factors for postpartum depression. 29 In the early postpartum period, mothers and infants navigate a critical neuroendocrine transition from pregnancy to lactation, and the shared neuroendocrine mechanism is hypothesized to contribute to both lactation failure and perinatal mood disorders. 30 In this trial, we found that acupoint hot compress significantly increased the breastfeeding milk volume when measured at 28.5, 52.5, and 76.5 hours after delivery, and depressive symptoms were significantly decreased when measured at 76.5 hours.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Although breastfeeding can protect individuals from postpartum depression, it was not found to be associated with incomplete breastfeeding in some studies, and there were other risk factors for postpartum depression. 29 In the early postpartum period, mothers and infants navigate a critical neuroendocrine transition from pregnancy to lactation, and the shared neuroendocrine mechanism is hypothesized to contribute to both lactation failure and perinatal mood disorders. 30 In this trial, we found that acupoint hot compress significantly increased the breastfeeding milk volume when measured at 28.5, 52.5, and 76.5 hours after delivery, and depressive symptoms were significantly decreased when measured at 76.5 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Terdapat dua penelitian dalam studi literatur ini yang tidak membuktikan hubungan antara kesehatan mental maternal dan praktik menyusui. Penelitian (Suzuki, 2020) Sebagian besar penelitian longitudinal yang menggunakan jumlah sampel besar memperlihatkan hubungan antara kesehatan mental perinatal terhadap luaran menyusui. Penelitian longitudinal lainnya juga menjelaskan adanya hubungan kasualitas dua arah antara kesehatan mental perinatal dan luaran menyusui.…”
Section: Metode Penelitianunclassified